2009
DOI: 10.1677/erc-09-0043
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of adiponectin and leptin in breast cancer: clinical and in vitro studies

Abstract: Obesity is a risk factor for breast cancer development. A recent hypothesis suggests that the adipokines, adiponectin and leptin, are involved in breast cancer development. This prompted us to investigate the role of adiponectin and leptin in mammary carcinogenesis. Adiponectin receptors (AdipoR1 and AdipoR2) and leptin receptor (Ob-Rt, representing all the isoforms of Ob-R) proteins were detected by immunohistochemistry in in situ ductal carcinoma, invasive ductal malignancy, and healthy adjacent tissue. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 56 publications
4
121
1
3
Order By: Relevance
“…T�� ������� �� ��p��� ��� A��p30 ��v��� �� ����v��u���, ������ ���� ��� ��p��� �� A��p30 ��v��� �����, ��� �������� �u�� p�������g���� ����g�� �� ��� ��v���p���� �� ������ (20). L�p��� ��� A��p30 �pp��� �� �x��� ����g������� ����v����� �� downregulating expression of each other's receptor and corre�p�����g ��g�����g p������� (8,39 …”
Section: Expression Ofunclassified
See 1 more Smart Citation
“…T�� ������� �� ��p��� ��� A��p30 ��v��� �� ����v��u���, ������ ���� ��� ��p��� �� A��p30 ��v��� �����, ��� �������� �u�� p�������g���� ����g�� �� ��� ��v���p���� �� ������ (20). L�p��� ��� A��p30 �pp��� �� �x��� ����g������� ����v����� �� downregulating expression of each other's receptor and corre�p�����g ��g�����g p������� (8,39 …”
Section: Expression Ofunclassified
“…A��p30 �� � 30-�D� p������ ���� ��v���� ��������� ����v�����, including anti-diabetic, anti-inflammatory and anti-atherogenic �u�������, ��� ��� ����� �������� �� ��v� ����-�u��� ������� �� ��v���� ��p�� �� ������ (8). I� �� ��� ���� ��u����� p������ ��������z�� �� ���p��� ����u�, ���� p����� �������������� ���g��g ���� 2 �� 30 µg/�� (9), �u� �� p�����x������ ���u��� �� ������� ��� ��u� g�������� ��u�� �� �� ��g���v��� ���������� ���� ���� ��� ���� (10).…”
Section: Introductionunclassified
“…2010) and LEP has been shown to down regulate AdipoR1 mRNA in breast cancer cells (Jarde et al. 2009). We found that overexpressing AdipoR1 was able to abolish the effects of the HFD‐CM on all cell‐cycle proteins measured (Figs 3 vs. 4) as well as overall cell‐cycle status (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2002, 2006; Jarde et al. 2009). LEP is predominately produced by white adipose tissue and its level in the peripheral circulation is directly proportional to BMI (Wauters et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation